(3GdfXGe GdbGfhfj ddeYQaI GdafjI ceMd YbO fbd GdJcfhdhLjG (B: s (3OQGSI ebGQfI (B/ s - (3agO UGdM Ydj GdNjGWs; (3SejMI eUWai GdbdjhHj s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2012)
(3JJfGhd gPg GdQSGdI HjGf eG gjI GdeYQaI GdafjI ceMd YbO fbd GdJcfhdhLjG(B: (3MjK JYQVJ dJYQja GdeYQaI GdafjI aj GdCfXeI GdebGQfI h Ydi GdeSJhi GdOhdj(B: (3h bO GJVM CfgG JMJhj Ydi eLehYI ef GdYfGUQ (B: (3GdeYdheGJ GdafjI(B: (3h GdCSGdjH GdUfGYjI(B: (3h GdNHQI GdafjI(B. (3ceG JHjf Cf NUGFU GdeYQaI GdafjI gj GdSQjI(B: (3h GdLOI(B: (3h GdbGHdjI ddfbd(B. (3h JYQVJ GdOQGSI ddWHjYI GdbGfhfjI ddeYQaI GdafjI h JejjRgG Yf GdCfXeI GdeTGHgI h GJVM Cf GdbGfhf GdaQfSj dG jYJQa HedcjI GdeYQaI GdafjI(B: (3Ydi YcS GdbGfhf GdCeQjcj GdPj PgH Edi GdGYJQGa GdcGed HedcjI GdeYQaI GdafjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2012s
(3HHdjhLQGajG(B: (3UaMGJ (B482-510s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdJQHSs; (3GjOcGSs; (3YbO fbd GdJcfhdhLjGs; (3GdGSJZdGd GdUfGYjs; (3GdTQcGJ eJYOOI GdbhejGJ chSjdI dfbd GdeYQaIs; (3GdeYQaI GdafjI aj YbO fbd GdJcfhdhLjGs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs